[11C]dihydrotetrabenazine Positron Emission Tomography in Manganese-Exposed Workers. Issue 10 (October 2020) - Criswell, Susan R.; Nielsen, Susan Searles; Warden, Mark N.; Perlmutter, Joel S.; Moerlein, Stephen M.; Sheppard, Lianne; Lenox-Krug, Jason; Checkoway, Harvey; Racette, Brad A.
Abstract : Objective: To understand the neurotoxic effects of manganese (Mn) exposure on monoaminergic function, utilizing [ 11 C]dihydrotetrabenazine (DTBZ) positron emission tomography (PET) to measure vesicular monoamine transporter 2 (VMAT2). Methods: Basal ganglia and thalamic DTBZ binding potentials (BPND) were calculated on 56 PETs from 41 Mn-exposed workers. Associations between cumulative Mn exposure, regional BPND, and parkinsonism were examined by mixed linear regression. Results: Thalamic DTBZ BPND was inversely associated with exposure in workers with less than 3 mg Mn/m 3 -yrs, but subsequently remained stable. Pallidal DTBZ binding increased in workers with less than 2 mg Mn/m 3 -yrs of exposure, but decreased thereafter. Thalamic DTBZ binding was inversely associated with parkinsonism ( P  = 0.003). Conclusion: Mn-dose-dependent associations with thalamic and pallidal DTBZ binding indicate direct effects on monoaminergic VMAT2. Thalamic DTBZ binding was also associated with parkinsonism, suggesting potential as an early biomarker of Mn neurotoxicity. Abstract : Supplemental Digital Content is available in the text